Evaluasi Kebijakan Fasilitas Pajak untuk Mendorong Riset dan Inovasi di Indonesia - Bhuana, Bhima Chandra; Ardiansyah, Benny Gunawan (Directorate General of Taxes, 2025)
The government of the Republic of Indonesia has implemented tax facilities to encourage businesses and industries to conduct research and development to optimize Indonesia's economic growth. Still, taxpayers have not widely benefited from these facilities. This study aims to explore the relevance of the tax facility policy to research and innovation activities in Indonesia and evaluate the implementation problems. Grounded on Sabatier and Mazmanian's public policy implementation framework, data were collected and analyzed using a qualitative research method, through a series of interviews with policy actors. The study found that: (1) the tax facility policy has minor relevance to the encouragement of research and innovation activities in Indonesia due to the problem of the unestablished science and technology ecosystem (2) the regulatory aspect of PMK Number 153/PMK.010/2020 has not provided adequate support for implementing ministries/agencies in addressing the socio-economic challenges of Indonesian society, as well the negative attitudes and perceptions of businesses and industries towards the policy. The findings are expected to stimulate further discussion on research and innovation in Indonesia to complete the factual basis that the government can use in determining future policy directions.